Taking snapshots of the jet-ISM interplay with ALMA. Issue Volume 15:Issue S359(2020) (March 2019) - Morganti, Raffaella; Oosterloo, Tom; Tadhunter, Clive N.
Abstract: We present an update of our ongoing project to characterise the impact of radio jets on the interstellar medium (ISM). This is done by tracing the distribution, kinematics and excitation of the molecular gas at high spatial resolution using ALMA. The radio active galactic nuclei (AGN) studied are in the interesting phase of having a recently born radio jet. In this stage, the plasma jets can have the largest impact on the ISM, as also predicted by state-of-the-art simulations. The two targets we present have quite different ages, allowing us to get snapshots of the effects of radio jets as they grow and evolve. Interestingly, both also host powerful quasar emission, making them ideal for studying the full impact of AGN. The largest mass outflow rate of molecular gas is found in a radio galaxy () hosting a newly born radio jet still in the early phase of emerging from an obscuring cocoon of gas and dust. Although the molecular mass outflow rate is high (few hundred), the outflow is limited to the inner few hundred pc region. In a second object (), the jet is larger (a few kpc) and is in a more advanced evolutionary phase. In this object, the distribution of the molecular gas is reminiscent of what is seen, on larger scales, in cool-core clusters hosting radio galaxies. Interestingly, gas deviating from quiescent kinematics (possibly indicating an outflow) is not very prominent, limited only to the very inner region, and has a low mass outflow rate. Instead, on kpc scales, the radio lobes appear associated with depressions in the distribution of the molecular gas. This suggests that the lobes have broken out from the dense nuclear region. However, the AGN does not appear to be able, at present, to stop the star formation observed in this galaxy. These results support the idea that the effects of the radio source start in the very first phases by producing outflows which, however, tend to be limited to the kpc region. After that, the effects turn into producing large-scale bubbles which could, in the long term, prevent the surrounding gas from cooling. Thus, our results provide a way to characterise the effect of radio jets in different phases of their evolution and in different environments, bridging the studies done for radio galaxies in clusters.